Insight in Offenders with Schizophrenia: Relationship to Psychopathology and Cognitive Function - Othman, Zahiruddin; Huri, Surina Zaman (Japan International Cultural Exchange Foundation, 2017)
Objectives: To study the insight in offenders with schizophrenia and its relationship of psychopathology and cognitive function. Methods: Seventy consecutive offenders with schizophrenia (aged 18-65) admitted to Hospital Bahagia Ulu Kinta within a six-month period were studied. Subjects' insight, psychopathology and cognitive function were assessed using the Insight and Treatment Attitude Questionnaire (ITAQ), Positive and Negative Syndrome Scale (PANSS), and Mini Mental State Examination (MMSE) respectively. Results: High PANSS positive scores were significantly associated with unsoundness of mind (p = 0.011). Low ITAQ and MMSE scores were significantly associated with PANSS total, negative and general scores. Conclusion: Positive symptoms were significantly associated with unsoundness of mind. Poor insight and cognitive function were significantly associated with negative symptoms as well as general and global psychopathology. This study however, failed to find significant insight-unsoundness of mind or insight-cognitive function relationships.